Communication in Public Health Programs: The Leprosy Project in India - Mukherji, Supriya; Priyadarshi, Meera; Singh, Suneeta (World Bank, Washington, DC, 2013)
The use of communication by the leprosy program in India offers valuable lessons for other programs, both in terms of its successes as well as the challenges ahead. The information, education and communication component has made a significant contribution in reducing the prevalence rate of leprosy cases. It has raised awareness about the signs and symptoms of leprosy and the importance of seeking early treatment, and reduced the social stigma associated with the disease. In recent years, the program emphasis has shifted to early voluntary self-reporting. The Government of India has set itself the goal of eliminating leprosy at the national level by December 2005. In the last vital year, cost-effective communication efforts have to be planned and sustained in collaboration with key partners to improve service delivery to hard-to-reach groups, motivate general health system staff, and ensure district-level political support.